An Investigation of Correlation of the Physician-Patient Relationship and Religious Orientation with Adherence to Treatment of Adolescents with Type 1 Diabetes - Qamar Kiani; Zahra Papailou (Health, Spirituality and Medical Ethics, 2016)
Background and Objectives: Metabolic control and observance of dietary therapy in adolescents with type I diabetes is weaker compared to other patients—the fact which might lead to physical, mental, and social changes in such adolescents in this period of their life. Hence, adolescences are more subject to complications of diabetes. This study, accordingly, was conducted to examine the relationship of religious orientation and physician-patient relations in prediction of treatment in adolescents with type 1 diabetes.